2018
DOI: 10.1097/txd.0000000000000835
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Donor Age on Clinical Outcomes of Primary Single Kidney Transplantation From Maastricht Category-III Donors After Circulatory Death

Abstract: BackgroundStandard-criteria donation after circulatory death (DCD) kidney transplants (KTx) have higher primary nonfunction, delayed graft function (DGF), and rejection rates than age-matched donation after brain death (DBD) but similar graft survival. Data on expanded-criteria DCD are conflicting and many centers remain concerned regarding their use.MethodsIn this single-center observational study with 5-year follow-up, we analyzed data from 112 primary DCD Maastricht category-III single KTx receiving similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…Overall, ECD–DCDs have shown poorer patient and graft outcomes compared with SCD–DCDs, but not inferior to ECD–DBDs [ 6 , 17 , 29–31 , 34 ]. The 3-year death-censored graft survival for ECD–DCD kidneys is 70–90% [ 6 , 30 , 31 , 35 ]. In our study, elderly cDCD kidneys showed good medium-term graft survival (88%), comparable to that from young cDCD and elderly DBD kidneys (90 and 80%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, ECD–DCDs have shown poorer patient and graft outcomes compared with SCD–DCDs, but not inferior to ECD–DBDs [ 6 , 17 , 29–31 , 34 ]. The 3-year death-censored graft survival for ECD–DCD kidneys is 70–90% [ 6 , 30 , 31 , 35 ]. In our study, elderly cDCD kidneys showed good medium-term graft survival (88%), comparable to that from young cDCD and elderly DBD kidneys (90 and 80%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that recipients of older DCD kidneys had inferior outcomes compared to those of young DCD or older donation after brain death (DBD) kidneys. DCD donor kidneys from older donors were more likely to have delayed graft function and lower estimated GFR (eGFRs) at 1‐year posttransplant compared to recipients of young DCD 9‐11 and older DBD kidneys 6,10‐13 . Recipients of older DCD kidneys had worse graft and patient survival 5‐years posttransplant compared to those of young DCD kidneys 11,14 .…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these studies were single‐center or national registry studies from other countries, which may have limited generalizability to US populations. Furthermore, patients evaluating an older DCD kidney offer are not choosing between an older DCD kidney and a healthier kidney; instead, they are choosing between accepting the current offer or waiting for a better offer that may never come 6,9‐13 . Studies on extended criteria deceased donor transplants have also identified recipient characteristics such as age, race, and time on dialysis as independent risk factors for inferior graft survival 15 and delayed graft function 16 .…”
Section: Introductionmentioning
confidence: 99%
“…As such, an increasing number of so-called marginal kidneys are now being transplanted into high-risk recipients. The main consequence of this aggressive policy is a striking rise in the incidence of delayed graft function (DGF) [ 1 , 2 , 3 ]. Clinically defined as the need for dialysis during the first post-transplant week, DGF is a complex entity that can negatively affect both patient and allograft survival [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lymphodepleting agents such as polyclonal rabbit anti-thymocyte globulin (rATG) or alemtuzumab (a monoclonal antibody targeting CD52) have been increasingly used in ECD and DCD KT to reduce the risk of rejection associated with IRI and minimize calcineurin inhibitor (CNI) exposure. Current data demonstrate excellent results in term of early acute rejection rates and successful CNI sparing, but the overall impact on DGF and long-term transplant survival remain marginal [ 2 , 3 , 28 , 29 ]. Peri-operative administration of complement inhibitors represent another feasible option as the complement system plays a key role in IRI, antigen presentation, and allograft rejection [ 6 ].…”
Section: Introductionmentioning
confidence: 99%